European success stories in industrial mathematics - Lery, Thibaut; Tewkesbury, Heather; Primicerio, Mario; Esteban, Maria J.; Fontes, Magnus; Maday, Yvon; Mehrmann, Volker; Quadros, Gonçalo; Schilders, Wil; Schuppert, Andreas (Springer, 2011)
This unique book presents real world success stories of collaboration between mathematicians and industrial partners, showcasing first-hand case studies, and lessons learned from the experiences, technologies, and business challenges that led to the successful development of industrial solutions based on mathematics. These success stories show the crucial contribution of mathematics to innovation and to the industrial creation of value, and the key position of mathematics in the handling of complex systems, amplifying innovation. Each story describes the challenge that led to the industrial cooperation, how the challenge was approached and how the solutions were achieved and implemented. When brought together, they illustrate the versatile European landscape of projects in almost all areas of applied mathematics and across all business sectors. This book of success stories has its origin in the Forward Look about Mathematics and Industry that was funded by the European Science Foundation (ESF) and coordinated by the Applied Mathematics Committee of the European Mathematical Society (EMS). In each of these success stories, researchers, students, entrepreneurs, policy makers and business leaders in a range of disciplines will find valuable material and important lessons that can be applied in their own fields.